Access to silicon(II)- and germanium(II)-indium compounds - Pahar, Sanjukta; Karak, Suvendu; Pait, Moumita; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2018)
Despite the remarkable ability of N-heterocyclic silylene to act as a Lewis base and form stable Lewis adducts with group 13 elements such as boron, aluminum, and gallium, there has been no such comparable investigation with indium and the realization of a stable silylene-indium complex has still remained elusive. Similarly, a germylene-indium complex is also presently unknown. We describe herein the reactions of [PhC(NtBu)(2)SiN-(SiMe3)(2)] (1) and [PhC(NtBu)(2)GeN(SiMe3)(2)] (4) with InCl3 and InBr3 that have resulted in the first silylene-indium complexes, [PhC(NtBu)(2)Si{N(SiMe3)(2)}-> InCl3] (2) and [PhC(NtBu)(2)Si{N(SiMe3)(2)}-> InBr3] (3), as well as the first germylene-indium complexes, [PhC(NtBu)(2)Ge{N(SiMe3)(2)}-> InCl3] (5) and [PhC(NtBu)(2)Ge{N(SiMe3)(2)}-> InBr3] (6). The solid-state structures of all species have been validated by single-crystal X-ray diffraction studies. Note that 5 and 6 are the first structurally characterized organometallic compounds that feature a Ge-In single bond (apart from the compounds in Zintl phases). Theoretical calculations reveal that the Si(II)-> In bonds in 2 and 3 and the Ge(II)-> In bonds in 5 and 6 are dative bonds.

Amidinato germylene-zinc complexes: synthesis, bonding, and reactivity - Yadav, Sandeep; Kumar, Rohit; Raj, K. Vipin; Yadav, Prashant; Vanka, Kumar; Sen, Sakya S. (Chemistry-An Asian Journal, 2020)
Despite the explosive growth of germylene compounds as ligands in transition metal complexes, there is a modicum of precedence for the germylene zinc complexes. In this work, the synthesis and characterization of new germylene zinc complexes [PhC(NtBu)(2)Ge{N(SiMe3)(2)}-> ZnX2](2)(X= Br (2) and I (3)) supported by (benz)-amidinato germylene ligands are reported. The solid-state structures of2and3have been validated by single-crystal X-ray diffraction studies, which revealed the dimeric nature of the complexes, with distorted tetrahedral geometries around the Ge and Zn center. DFT calculations reveal that the Ge-Zn bonds in2and3are dative in nature. The reaction of2with elemental sulfur resulted in the first structurally characterized germathione stabilized ZnBr(2)complexes PhC(NtBu)(2)Ge(=S){N(SiMe3)(2)}-> ZnBr2(5). Therefore, the Ge=S in5is in-between Ge-S single and Ge=S double bond length, owing to the coordination of a sulfur lone pair of electrons to ZnBr2.
Keywords: DFT; Germathione; Germylene; X-ray Structure; zinc

Antimicrobial two-dimensional covalent organic nanosheets (2D-CONs) for the fast and highly efficient capture and recovery of phosphate ions from water - Dey, Subhasis; Das, Sribash; Patel, Anjali; Raj, K. Vipin; Vanka, Kumar; Manna, Debasis (Journal of Materials Chemistry A, 2022)
The retrieval of depleting resources from wastewater could help resolve the mounting demands for resources in our society. Phosphate is an essential nutrient for all living things. However, the diminution of global reserves of phosphate rock could significantly affect our food security in the near future. At the same time, the removal of phosphates and pathogens is of great importance for water security and de-eutrophication. The specific pH-dependent adsorption and desorption of phosphate ions by water-insoluble adsorbents is an exciting strategy for removing and recovering phosphates from contaminated water. Herein, we report the development of new two-dimensional guanidine-containing covalent organic nanosheets (2D-gCONs). This water-insoluble amorphous polymer (exfoliated) selectively sequestered phosphate ions in the presence of other competing anions and could be reused for multiple cycles. The polymer showed a fast removal of phosphate ions with a maximum adsorption capacity of 398 mg g(-1) (pH 7.0). The sequestered phosphate ions could be easily reclaimed, and the polymer could be recycled just by altering the pH (similar to 10.0) of the aqueous solution. The guanidinium moieties played a pivotal role in exfoliation in aqueous medium and in the antibacterial activities against Gram-negative and Gram-positive bacteria. We hypothesize that the current study may advance the design of water-insoluble CONs to remove and recover phosphate ions from wastewater and could help alleviate the negative impact of water eutrophication. This strategy can also be tweaked to address other severe environmental challenges.